2018
DOI: 10.1186/s12886-018-0878-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of transpupillary silicone oil removal in combination with micro-incision phacoemulsification cataract surgery: comparison with 23-gauge approach

Abstract: BackgroundTo evaluate safety and efficacy of transpupillary silicone oil removal combined with micro-incision phacoemulsification cataract surgery, and to compare results of transpupillary with 23-gauge three-port vitrectomy approach.MethodsConsecutive cases that underwent silicone oil removal using either transpupillary or three-port approach in combination with micro-incision phacoemulsification cataract surgery were retrospectively reviewed. The main outcome measures were postoperative detachment rate, sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Xu et al transpupillary removal vs. pars plana SO removal combined with standard phaco-cataract removal. The study found that early IOP was lower with transpupillary approach however this approach does not allow management of new posterior segment pathology found intraoperatively [47].…”
Section: Discussionmentioning
confidence: 83%
“…Xu et al transpupillary removal vs. pars plana SO removal combined with standard phaco-cataract removal. The study found that early IOP was lower with transpupillary approach however this approach does not allow management of new posterior segment pathology found intraoperatively [47].…”
Section: Discussionmentioning
confidence: 83%
“…o No recurrent retinal detachment. It is difficult to unequivocally comment on more than 15% of recurrent retinal detachment, described by Xu et al after oil removal via the anterior chamber [6]. Such a large difference, i.e., the lack of recurrent retinal detachment in the described group, may be due to the fact that all procedures were performed by one surgeon, including qualification for silicone oil removal, or the use of passive oil removal technique, not active aspiration as described by Xu.…”
Section: B Postoperative Complicationsmentioning
confidence: 84%
“…o Significant reduction of the procedure duration. So, removal via a 2-2.5 mm incision is much more effective than via a pars plana 0.9-0.5 mm incision, even when using the active aspiration technique [6].…”
Section: B Postoperative Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one of commonly used and feasible method is the removal of silicone oil (ROSO) as soon as the retina stabilizes. 6 Unfortunately, in many cases, silicone oil may not be removed for a while and consequently develop a posterior cataract. Thus, oil and cataract extraction surgery is the only method to restore the vision of the patient.…”
Section: Introductionmentioning
confidence: 99%